Structural analysis of the gallery forest of Capetinga stream, in Brasília, Brazil, habitat of Callithrix jacchus penicillata L. - Seabra, Hamed Farias; Encinas, José Imaña; Felfili, Jeanine Maria (Pesquisa Agropecuaria Brasileira, 1991)
A structural survey of one stretch of the gallery forest of Capetinga stream (Brasília, Brazil) through a 100 m transect was carried out. The species preferred by Callithrix jacchus penicillata L. were identified. Eighty four trees corresponding to 28 species were measured. The main species were Callisthene major Mart., Copaifera langsdorffii Desf., Emmotum nitens Miers., Tapirira guianensis Aubl., and Sclerolobium paniculatum Vog. which presented high nummer of trees and importance value index. The species Callisthene major Mart., Tapirira guianensis Aubl. and Vochysia pyramidalis Mart. presented scars at the stems and branches produced by the primate Callithrix jacchus penicillata L., which can be identified as being part of Callithrix jacchus penicillata L. source of nourishment.